2022
DOI: 10.1039/d2nr00944g
|View full text |Cite
|
Sign up to set email alerts
|

MBE-grown ultrathin PtTe2 films and their layer-dependent electronic structures

Abstract: Two-dimensional (2D) platinum ditelluride (PtTe2) has received significant attention for 2D photodetector applications due to its novel physical properties. One of the critical factors that affect device performance is the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…PtTe 2 was grown by molecular beam epitaxy. This approach has been shown by several groups to result in high quality PtTe 2 films down to monolayer thickness if grown at low (250 °C) temperatures. , Growth at temperatures above 300 °C favors formation of bilayer thick islands Figure shows the as grown PtTe 2 film, that consists of both mono- and bilayer islands.…”
mentioning
confidence: 98%
“…PtTe 2 was grown by molecular beam epitaxy. This approach has been shown by several groups to result in high quality PtTe 2 films down to monolayer thickness if grown at low (250 °C) temperatures. , Growth at temperatures above 300 °C favors formation of bilayer thick islands Figure shows the as grown PtTe 2 film, that consists of both mono- and bilayer islands.…”
mentioning
confidence: 98%
“…Figures d–f present the optical microscopy, scanning electron microscopy, and atomic force microscopy images of as-grown PtTe 2 single crystals in regular hexagonal geometry, respectively. The Raman spectrum (see Figure g) acquired from the representative as-grown PtTe 2 nanoflakes shows two characteristic modes centered at 114.2 and 157.4 cm –1 , which are assigned to the E g and A 1g modes of PtTe 2 , respectively. , Moreover, to confirm the chemical compositions of the sample, we conducted EDS elemental analysis and mappings characterizations, as shown in Figure S1. The results confirm the synthesis of PtTe 2 in the stoichiometric ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The interlayer separation (see Figure b) between MoS 2 and bilayer PtTe 2 (i.e., bulk material) is calculated to be 3.2 Å, which is smaller than that of MoS 2 –graphene (3.4 Å). The small interlayer spacing between MoS 2 and bilayer PtTe 2 leads to covalent-like ultrastrong forces benefiting from the strong thickness-dependent nature of PtTe 2 . ,, It is reported that PtTe 2 layers would evolve from semiconductive to metallic as the thickness increases owing to strong interlayer interactions, which provides complementary proof to our claim . The differential charge density for the MoS 2 /PtTe 2 heterostructure (see Figure c) displays obvious charge redistribution at the interfacial layer, further indicating strong interlayer coupling between MoS 2 and PtTe 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the Pt-tellurides have many attractive attributes that allow us to gain better fundamental understanding of van der Waals (vdW) materials and their potential applications. The Pt-tellurides have attracted interest for: (i) layer-dependent electronic properties that cause opening of a band gap in monolayer PtTe 2 , while the system otherwise is (semi)­metallic, (ii) topological features , for both PtTe 2 and Pt 3 Te 4 and a strong spin texture that unlike the topological states persist down to the monolayer, making them potentially interesting materials for spintronics applications, , and (iii) useful electrochemical properties for hydrogen evolution as well as oxygen reduction reactions. …”
mentioning
confidence: 99%